Dynamics of production parameters for zooplankton as the main component of forage base for nekton in the western Bering Sea - Elena P. Dulepova (Известия ТИНРО, 2014)
Production parameters of zooplankton are calculated and analyzed on the data of plankton surveys in the framework of BASIS-1 and BASIS-2 research projects conducted in the western Bering Sea in 2002-2013. Top-ten species forming the bulk of non-predatory zooplankton production are the copepods Calanus glacialis, Eucalanus bungii, Neocalanus plumchrus, Pseudocalanus minutus, Metridia pacifica, Oithona similis, and Neocalanus cristatus and euphausiids Thysanoessa inermis, Th. raschii , and Th. longipes . The arrowworm Sagitta elegans produces the main part of predatory zooplankton production. Functional characteristics of trophic groups and production of the whole zooplankton community depend on ratio of these mass species. During the surveyed period, the non-predatory zooplankton production was the highest in the northern part of the western Bering Sea (2531-3160 mg/m3yr) and the lowest in its deep-water part (944 mg/m3yr), whereas the predatory zooplankton production was the highest in the deep-water part of the Sea and over the western shelf. The portion of zooplankton production available for grazing by fish is estimated, and the areas with possible problems for planktivorous consumers are determined: all of them are located in the deep-water part of the western Bering Sea.